Targeting the chemerin/CMKLR1 axis by small molecule antagonist α-NETA mitigates endometriosis progression - Yu, Ming; Yang, Yali; Zhao, Hao; Li, Mengxia; Chen, Jie; Wang, Baobei; Xiao, Tianxia; Huang, Chen; Zhao, Huashan; Zhou, Wei; Zhang, Jian V. (Frontiers in Pharmacology, 2022)
Endometriosis is a common gynecological disease, characterized by the presence of en-dometrial-like lesions outside the uterus. This debilitating disease causes chronic pelvic pain and infertility with limited therapeutics. Chemerin is a secretory protein that acts on CMKLR1(Chemerin Chemokine-Like Receptor 1) to execute functions vital for immunity, adiposity, and metabolism. Abnormal chemerin/CMKLR1 axis underlies the pathological mechanisms of certain diseases including cancer and inflammatory diseases, but its role in endometriosis remains unknown. Herein, our results showed that chemerin and CMKLR1 are up-regulated in endome-triotic lesions by analyzing the human endometriosis database and murine model. Knockdown of chemerin or CMKLR1 by shRNA led to mesenchymal-epithelial transition (MET) along with compromised viability, migration, and invasion of hEM15A cells. Most importantly, 2-(α-naphthoyl) ethyltrimethylammonium iodide (α-NETA), a small molecule antagonist for CMKLR1, was evi-denced to exhibit profound anti-endometriosis effects (anti-growth, anti-mesenchymal features, anti-angiogenesis, and anti-inflammation) in vitro and in vivo. Mechanistically, α-NETA exhibited a dual inhibition effect on PI3K/Akt and MAPK/ERK signaling pathways in hEM15A cells and murine endometriotic grafts. This study highlights that the chemerin/CMKLR1 signaling axis is critical for endometriosis progression, and targeting this axis by α-NETA may provide new options for therapeutic intervention.